Lithium conductivity in glasses of the Li2O–Al2O3–SiO2 system. Issue 1 (13th November 2014) - Ross, Sebastian; Welsch, Anna-Maria; Behrens, Harald
Abstract : An Arrhenius plot for DC electrical conductivity of fully polymerized and depolymerized Li aluminosilicate glasses is one way to reflect the effect of local structure vs. lithium content. Abstract : To improve the understanding of Li-dynamics in oxide glasses, i.e. the effect of [AlO4 ] − tetrahedra and non-bridging oxygens on the potential landscape, electrical conductivity of seven fully polymerized and partly depolymerized lithium aluminosilicate glasses was investigated using impedance spectroscopy (IS). Lithium is the only mobile particle in these materials. Data derived from IS, i.e. activation energies, pre-exponential factors and diffusivities for lithium, are interpreted in light of Raman spectroscopic analyses of local structures in order to identify building units, which are crucial for lithium dynamics and migration. In polymerized glasses (compositional join LiAlSiO4 –LiAlSi4 O10 ) the direct current (DC) electrical conductivity continuously increases with increasing lithium content while lithium diffusivity is not affected by the Al/Si ratio in the glasses. Hence, the increase in electrical conductivity can be solely assigned to lithium concentration in the glasses. An excess of Li with respect to Al, i.e. the introduction of non-bridging oxygen into the network, causes a decrease in lithium mobility in the glasses. Activation energies in polymerized glasses (66 to 70 kJ mol −1 ) are significantly lower than those in depolymerized networks (76 to 78 kJ mol −1 ) while pre-exponential factors are nearly constant across all compositions. Comparison of the data with results for lithium silicates from the literature indicates a minimum in lithium diffusivity for glasses containing both aluminium tetrahedra and non-bridging oxygens. The findings allow a prediction of DC conductivity for a large variety of lithium aluminosilicate glass compositions.